Kashmir as a Symbol of Pakistan: Why Violence in Kashmir Never Stop? - Hwang, Wonjune (UI Scholars Hub, 2019)
Kashmir has been a 'powder keg' in South Asia. In this region, India and Pakistan waged three all-out wars and numerous skirmishes. Kashmir has been occupied separately since 1947, but still, both sides claim the other’s occupation is illegal. Muslim Kashmiris, who are allegedly supported by Pakistan, continuously commit terrorist acts, and in return, Indian officials in Jammu and Kashmir violently suppress demonstrations and commit human right violations. After 9/11 in 2001, terrorists have become demonized and pardonless. This article focuses on analyzing the sources of violence and Pakistani intervention. The idea of this article is theoretically based on Volkan's chosen trauma and symbol of identity. Continuous massacres and discriminations in Kashmir committed by Hindu Indians have formed the identity of Pakistanis as the chosen trauma, and current discriminations and persecutions reactivate their fear and anger. Cessation of the violence must be the priority on Kashmir issue. For this, discriminations and persecutions should be suspended.